STRUCTURE OF THE ORTHOCLASE (001)- AND (010)-WATER INTERFACES BY HIGH-RESOLUTION X-RAY REFLECTIVITY - Fenter P.; Cheng L.; Park C.; Zhang Z.; Sturchio N.C. (My University, 2003)
High-resolution in situ X-ray specular reflectivity was used to measure the structures of orthoclase (001) and (010) cleavage surfaces in contact with deionized water at 25°C. X-ray reflectivity data demonstrate a high degree of structural similarity between these two orthoclase-water interfaces. Both interfacial structures include cleavage along the plane of minimal bond breakage resulting in surfaces terminated by non-bridging oxygens; structured water within 5 A of the orthoclase surface (consisting of adsorbed species at the surface and layered water above the surface), with a featureless water profile beyond 5 A; substitution of outermost K+ ions by an oxygen containing species (presumably H3O+); and small structural displacements of the near surface atoms. The interfacial water structure, in comparison with recent results for other mineral-water interfaces, is intermediate between the minimal structure found at calcite-, barite-, and quartz-water interfaces and the more extensive structure found at the muscovite-water interface.